Sexual selection in the Swallow Hirundo rustica - A review - Bańbura, Jerzy (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2005)
Darwinian theory of sexual selection and its development up to the present state of knowledge are sketched. The most important results of empirical studies on sexual selection in the Swallow Hirundo rustica are reviewed. The Swallow is a socially monogamous, slightly sexually dimorphic avian species. Long tail streamers are considered as sexual ornaments of males. Female preference for long and symmetric male tails has been inferred on both observational and experimental grounds. Experimental elongation of the tail causes short-term benefits and long-term costs in male reproductive performance. Behavioural consequences of sexual selection acting in the Swallow are discussed. An aerodynamic role of male tail streamers is also considered.